FAUNAL COMPOSITION AND ECOLOGICAL SIGNIFICANCE OF COLEOPTERA IN THE KYZYLKUM DESERT, KARAKALPAKSTAN, UZBEKISTAN - Bekbanov A. Zh. (Web of Journals Publishing, 2025)
The Kyzylkum Desert, located in the Republic of Karakalpakstan, Uzbek- istan, represents a unique arid ecosystem characterized by extreme environmen- tal conditions. This study examines the faunal composition and ecological roles of Coleoptera (beetles) within this desert, with a particular focus on the family Carabidae (ground beetles). Field surveys conducted between 2023 and 2024 in various landscapes of the Kyzylkum Desert, including sandy dunes, clay plains, and tugai forests, revealed a diverse beetle fauna. A total of 31 species across 8 families were recorded, with Carabidae being the most abundant and ecologically significant. Ground beetles were found to play a critical role as entomophages, regulating pest populations of agricultural importance. This paper discusses the biodiversity, distribution, and ecological interactions of Coleoptera in the context of the desert’s environmental challenges and highlights their importance for ecosys- tem stability and agricultural management. Recommendations for further research and conservation are provided.
Keywords: Coleoptera, Carabidae, Kyzylkum Desert, Karakalpakstan, biodi- versity, entomophages.